A study exploring the experiences of women and imposter syndrome - Kingan, Anneka Samantha (2020)
With an increase in focus on females in the workplace, this research project explores the experiences of females and their relationship with imposter syndrome, and examines the definition of imposter syndrome, its causes and consequences for those suffering from it. The paper makes recommendations to help sufferers manage their imposter syndrome recommendations for companies to implement to reduce cases of imposter syndrome developing in the workplace.